Is It Possible to Treat, and Under Which Circumstances, Presence of Aflatoxin as Criminal Acts? - Joldžić, Vladan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
Aflatoxins, toxins produced by fungi: Aspergillus flavus and Aspergillus parasiticus, have attracted scientific attention and the attention of the public as well as the state apparatus for nearly five decades. States itsef, or by coordinated efforts (as in European Union), forms legislatures by which regulate relations toward numerous kinds of aflatoxins (espettialy: B, G, or M) and their species (subvarieties) having in minds that aflatoxins itself or in conjunction with some other factors produce solid number of medical problems, between them hepatitis (A, B and C) and liver caner. Knowing that the Republic of Serbia, for many years, had adequate legal and sub-legal acts of importance for aflatoxins and that, starting from the year 2013, numerous sub-legal acts of doubtful values, with standards to the 10, later 5, times different from the earlier which had been more than 20 years harmonized with the EU standards, this attraced our attention to ansver on the question: Is it possible to start criminal procedure against subjetcs which offend norms that regulate relations tovard aflatoxins? This text is our descriptive and analytical effort to formulate some answers to this actual and important question.